2018
DOI: 10.1111/anec.12610
|View full text |Cite
|
Sign up to set email alerts
|

TWARMI pilot trial: The value and optimal criteria of microvolt T‐wave alternans in the diagnosis of reversible myocardial ischemia in patients without structural cardiac disease

Abstract: Part of article was presented on Dubrovnik ESC highlights 2015 as a poster presentation and won the first price.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…The number of subjects with multi-VD in the abnormal TWA value group was higher than the number in the other group, 44 subjects vs 35 subjects respectively. Eventhough it was not statistically significant, the result is similar with the study that mentioned there will be higher TWA value if there is more vessels with significant stenosis (Puljevic et al, 2019).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The number of subjects with multi-VD in the abnormal TWA value group was higher than the number in the other group, 44 subjects vs 35 subjects respectively. Eventhough it was not statistically significant, the result is similar with the study that mentioned there will be higher TWA value if there is more vessels with significant stenosis (Puljevic et al, 2019).…”
Section: Resultssupporting
confidence: 85%
“…Myocardial ischemia and infarction cause slowed repolarization and manifest as changes of the ST-segment and T-wave in the electrocardiogram (ECG) (Li et al, 2021). One of the most potential ECG parameter is the TWA, which detects beat to beat morphological and amplitude changes of the T wave (Janusek et al, 2015;Puljevic et al, 2019;Verrier & Nieminen, 2010). TWA has a one-year negative predictive value (near 95%) for ventricular arrhythmia (Narayan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding ECG repolarization, instability markers measuring microvolt T wave alternans have been shown to take higher values in CAD patients than in healthy subjects and also in CAD patients with significant stenosis than in patients with no major stenosis [29,30]. These results were confirmed in subsequent studies, which additionally revealed greater accuracy of T wave alternans when compared with conventional ST segment analysis for CAD detection [31]. Other repolarization markers, like the QT interval, HR-corrected QT interval (QTc) and spatial QT dispersion have been explored prior to, during and after stress testing in a large cohort of patients undergoing coronary angiography [32].…”
Section: Discussionmentioning
confidence: 63%
“…Prolonged radiation exposure leads to capillary network and myocardium damage, eventually contributing to the development of myocardial, heart valve, and cusp fibrosis ( 12 ). Given that lung cancer has been known to have a higher risk of cardiovascular events, potential biomarkers to indicate susceptibility to heart ischemia need to be identified ( 13 ).…”
Section: Introductionmentioning
confidence: 99%